2018
DOI: 10.1071/an16258
|View full text |Cite
|
Sign up to set email alerts
|

Methionine supplementation of low-protein diet and subsequent feeding of low-energy diet on the performance and blood chemical profile of broiler chickens

Abstract: The effects were investigated of supplementing methionine (Met) in a low-crude protein diet (Low-CP+Met) during Days 11–24 post-hatch and subsequent feeding with a low-metabolisable energy diet (Low-ME; –0.31 MJ/kg) during Days 25–42 on the productive performance and blood chemistry profile of broiler chickens. The 1600 broiler chicks were divided into four groups and fed as follows: (1) Control diet; (2) Low-CP (Met deficiency) diet during Days 11–24, then re-feeding with conventional diet; (3) Low-CP+Met die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
3
0
3
Order By: Relevance
“…All reduced protein diet groups resulted in higher abdominal fat percentage compared to the SP2 group. This is in agreement with references [31][32][33], who reported increased abdominal fat caused by the reduced protein diet. Increased abdominal fat percentage in our experiment could be because of reduced protein and deficiency of methionine in the diet.…”
Section: Nitrogen Digestibilitysupporting
confidence: 93%
“…All reduced protein diet groups resulted in higher abdominal fat percentage compared to the SP2 group. This is in agreement with references [31][32][33], who reported increased abdominal fat caused by the reduced protein diet. Increased abdominal fat percentage in our experiment could be because of reduced protein and deficiency of methionine in the diet.…”
Section: Nitrogen Digestibilitysupporting
confidence: 93%
“…Improved knowledge of CP requirements for different animal species and categories through applying the concept of dietary formulations with ideal protein composition to optimize amino acid use is also needed. A decrease of greater than three or four percent in dietary CP, even if the feed meets all the amino acid requirements, may result in low productive performance [ 30 ]. Thus, determining the true dietary CP requirements for male Japanese quails is essential to correctly apply the optimal protein concept to breeder flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Hai-ming et al, (2015) reported that there were significant higher LBW of broilers chicks at 42 d of age between energy and protein decreasing. Jariyahatthakij et al, (2018) stated that when low CP and energy diets, the addition of Met improved LBW during the day (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The LBW of the control group was better than the other groups (P < 0.01).…”
Section: Economic Efficiencymentioning
confidence: 99%
“…Rajendran et al, (2015) showed that the energy and protein of the diet significantly affected BW, cumulative FI and FCR in broiler chickens. Jariyahatthakij et al, (2018) in low CP and energy diets, stated that the addition of Met improved growth performance and FCR during the day (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The growth performance of the control group was better than the other groups (P < 0.01).…”
Section: 4-feed Conversion Ratio (Fcr)mentioning
confidence: 99%